CaM kinase II-dependent mobilization of secretory granules underlies acetylcholine-induced stimulation of exocytosis in mouse pancreatic B-cells. - Gromada, J; Høy, M; Renström, E; Bokvist, K; Eliasson, L; Göpel, S; Rorsman, P (1999)
1. Measurements of cell capacitance were used to investigate the mechanisms by which acetylcholine (ACh) stimulates Ca2+-induced exocytosis in single insulin-secreting mouse pancreatic B-cells. 2. ACh (250 microM) increased exocytotic responses elicited by voltage-clamp depolarizations 2.3-fold. This effect was mediated by activation of muscarinic receptors and dependent on elevation of the cytoplasmic Ca2+ concentration ([Ca2+]i) attributable to mobilization of Ca2+ from intracellular stores. The latter action involved interference with the buffering of [Ca2+]i and the time constant (tau) for the recovery of [Ca2+]i following a voltage-clamp depolarization increased 5-fold. As a result, Ca2+ was present at concentrations sufficient to promote the replenishment of the readily releasable pool of granules (RRP; > 0.2 microM) for much longer periods in the presence than in the absence of the agonist. 3. The effect of Ca2+ on exocytosis was mediated by activation of CaM kinase II, but not protein kinase C, and involved both an increased size of the RRP from 40 to 140 granules and a decrease in tau for the refilling of the RRP from 31 to 19 s. 4. Collectively, the effects of ACh on the RRP and tau result in a > 10-fold stimulation of the rate at which granules are supplied for release.